Comparison of mechanical characteristics of different types of shales in the Ordos Basin - Dou, Liangbin; Chen, Jingyang; Zuo, Xiongdi; Liu, Yonghui; Sun, Lin; Fang, Yong; Cheng, Xuebin; Wang, Ting (Frontiers in Earth Science, 2023)
There are three kinds of shale in Ordos Basin, namely, laminated shale, sandwich shale and foliated shale. In this paper, the three different types of shales are studied in terms of mineral composition, mechanical properties and conductivity, and compared with neighboring sandstones. The study found that the foliated shale has the lowest content of rigid minerals (47.5%), lower elastic modulus and tensile strength (26.98 Gpa and 168.29 MPa, respectively), higher Poisson's ratio (0.25), the smallest brittleness index (0.48), and larger fracture toughness (0.42). The laminated shale has higher content of rigid minerals (68.50%), lowest elastic modulus and tensile strength (25.77Gpa and 122.46MPa, respectively), highest Poisson's ratio (0.26), highest brittleness index (0.56), lowest fracture toughness (0.18). The sandwich shale has the highest rigid mineral content (78.16%), the highest elastic modulus and tensile strength (35.31 Gpa and 197.37 MPa, respectively), the lowest Poisson's ratio (0.24), larger brittleness index (0.52), and larger fracture toughness (0.415). Furthermore, with the increase of coring angle, the elastic modulus of all three shales increases. In addition, with the increase of closing pressure and the decrease of sand laying concentration, the proppant embedding depth gradually increases, the conductivity decrease. This means that from the perspective of forming complex fracture networks, the fracturing effect of the foliated shale is unsatisfactory, while fracturing effect of the laminated shale and the sandwich shale is better. Moreover, it is recommended to prefer directional injection along vertical laminae or at high angles, which is conducive to the formation of complex fracture networks. For laminated shale with low strength, the sand laying concentration should be increased to ensure the conductivity of the fractured fracture.2 This is a provisional file, not the final typeset articleThis study provides some technical guidance for the identification of different types of shale fracturing desserts and fracturing process.